OUTCOME OF LARGE MENINGIOMA SURGERIES WITH PREOPERATIVE DIGITAL SUBTRACTION ANGIOGRAPHY (DSA): A CLINICAL STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Background: The management of large meningiomas presents unique challenges due to their size, vascularity, and potential proximity to critical neurovascular structures. Preoperative Digital Subtraction Angiography (DSA) is a diagnostic tool that can aid in surgical planning by providing detailed vascular maps of these tumors. This study investigates the outcomes of large meningioma surgeries managed with preoperative DSA. Methods: This prospective study included 15 patients with large intracranial meningiomas, of which 8 underwent preoperative embolization (embolization grp), and 7 did not (non-embolization grp). The outcomes assessed included the extent of tumor resection, operative time, intraoperative blood loss, and postoperative complications. Multivariate analyses were performed to identify factors associated with favourable outcomes. Results: Preoperative DSA provided valuable information that guided surgical strategy, particularly in achieving complete tumor resection. The overall rate of complete resection (Simpson grade I-II) was high, with 80% of patients achieving this outcome. The average operative time was 265.7 ± 70.3 minutes, and the mean intraoperative blood loss was 500.7 ± 200.4 mL. Postoperative complications were relatively low, with a complication rate of 30%. Conclusion: Preoperative DSA plays a crucial role in the management of large meningiomas by enhancing surgical planning and potentially improving surgical outcomes. The use of DSA allows for better visualization of the tumor’s vascular supply, aiding in the safe and effective resection of these challenging tumors.